EXPLORING THE PATTERN OF STROKE IN YOUNG ADULTS: CLINICAL PRESENTATIONS, RISK FACTORS, AND IMPLICATIONS FOR EARLY DETECTION AND MANAGEMENT (The Research of Medical Science Review, 2025)
Introduction: Stroke, traditionally viewed as a disease of the elderly, is increasingly recognized as a significant health concern among young adults.Objectives: The main objective of the study is to find the pattern of stroke in young adults’ clinical presentations, risk factors, and implications for early detection and management.Material and methods: This retrospective analysis was conducted in Mayo Hospital, Lahore. Data was collected from 220 stroke patients from different age groups. Medical records of eligible patients were systematically reviewed to extract pertinent information regarding demographics, clinical presentation, medical history, risk factors, diagnostic workup, treatment modalities, and outcomes. Conclusion: It is concluded that stroke poses a significant burden on young adults, with varying clinical presentations and risk factor profiles. Early recognition and comprehensive risk assessment are crucial for timely intervention and improved outcomes in this population.